Pengelolaan Waktu Belajar Siswa Berprestasi Berbasis Smartphone di Masa Pandemi Covid-19 - Azmi Rahmatullah; Sutama Sutama (Universitas Muhammadiyah Surakarta, 2021)
One of the effects of the Covid-19 pandemic was the disruption in education, namely the problem of teaching and learning and time management. Thus, teachers and students must find solutions to be able to manage learning time management and the media used for learning, namely smartphones. This certainly can be a very effective choice during the Covid-19 pandemic. This study aimed to describe the time management of student learning achievement, analyzing the relationship of learning time with student achievement, and analyzing the impact of smartphones on learning time and student achievement during the covid-19 pandemic. This type of research is a reference research that data retrieval is oriented to several appropriate references. The focus of this research is how effective time management and smartphone usage is for learning in the Covid-19 pandemic. The validity of the data in this article is with various sources and time extensions. The data analysis technique in this article is to use the constant comparison method. The results of the research in this article are three.1) Describe time management (study time). 2) Analysis of the relationship of learning time with student achievement. 3) Analyzing the impact of smartphones in time management and student achievement during the covid-19 pandemic.